2006
DOI: 10.1177/1744935906071909
|View full text |Cite
|
Sign up to set email alerts
|

Industrial districts as organizational environments: Resources, networks and structures

Abstract: Abstract:The paper combines economic and sociological perspectives on organizations in order to gain a better understanding of the forces shaping the structures of industrial districts (IDs) and the organizations of which they are constituted. To effect the combination , the resource based view (RBV) and resource dependency theory are combined to explain the evolution of different industry structures. The paper thus extends work by Toms and Filatotchev by spatializing consideration of resource distribution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…This pattern forecloses some choices and promotes others. Governance is particularly important to understanding change and adjustment as it has such a large role to play in freezing or unfreezing existing resource configurations (Popp et al, 2006). Thus, crucially these four factors not only drive the larger dynamic of the life cycle but also act as generators of potential sources of lock-in by creating the contexts within which actors frame and make choices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern forecloses some choices and promotes others. Governance is particularly important to understanding change and adjustment as it has such a large role to play in freezing or unfreezing existing resource configurations (Popp et al, 2006). Thus, crucially these four factors not only drive the larger dynamic of the life cycle but also act as generators of potential sources of lock-in by creating the contexts within which actors frame and make choices.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this relationship is, as we are taught both by life-cycle models and by the evolutionary economics of Nelson and Winter, a path-dependent one in which capabilities emerge and are elaborated at the level of both the firm and the district. Indeed, given both the importance of external economies to the logic of agglomeration and, in train, the importance of understanding districts as systems, the capabilities of the firm must be understood as being set within and, to an extent, dependent on those of the district as a whole (Popp et al, 2006).…”
Section: Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…Popps, Toms and Wilson (2006) emphasized how networks provided relational governance that constrained managerial opportunism, but also encouraged coordination, a point previously asserted by Toms and Filatotchev (2004). However, the benefits of networks extended beyond decreased transaction costs, and in later work Williamson (1985), for example, suggested that the relational and social interdependence which underpin networks provided efficiency benefits, and a 'communicative rationality' based upon learning processes upon which social relationships are founded (Boyce, 2003).…”
Section: Network Religion and Quakersmentioning
confidence: 96%
“…The dynamics of industrial regions are among the subjects that feature in the first volume. Popp et al. attempt to link firm‐based and cluster‐based theories using pre‐1914 British industrial districts as case studies, although they do concede the contingent and place‐specific nature of many outcomes, a point reinforced elsewhere by Martin and Sunley, who argue that the mechanisms whereby some regional clusters wither, whereas others regenerate, are still understood poorly. They underscore the vague conceptual underpinnings of terms like ‘path‐dependence’ and ‘lock‐in’.…”
Section: (V) 1850–1945
Mark Freeman and Julian Greaves
University Of mentioning
confidence: 99%